Workload Analysis Using the Full-Time Equivalent and Rating Scale Mental Effort Methods in the Production Division - Azizy, Annisa Rahmi; Rusindiyanto; Rizqi Novita Sari (Newinera Publisher, 2024)
CV Aurexell is an industry engaged in the food sector, namely bread. In the production process, several problems cause physical and mental workloads, where employees at dough-making, weighing, and molding workstations feel physically burdened because they have to work standing up for a day and mentally burdened because they have to meet production targets every day but there is a shortage of employees at the fermentation and baking, also cream filling workstations. To solve these problems, we must take workload measurements to find the optimal number of employees. Based on data processing using the FTE method, it is evident that the physical workload of all employees falls within the normal category, which ranges from 1 to 1.28, which means that the number of employees at CV Aurexell is optimal because the physical workload is normal. Based on data processing using the RSME method, it is evident that operators 7 and 9 have mental workloads of 85.33 and 83, respectively, classified as great effort. At the same time, other operators require rather much too considerable effort. The optimal number of workers in the RSME method is six people for the dough-making, weighing, and molding workstation, three for the fermentation and baking workstation, three for the cream-filling workstation, and thirteen for the packaging workstation.